The growing resistance of Klebsiella pneumoniae; the need to expand our antibiogram: a case report and review of the literature - Garbati, Musa Abubakar; Al Godhair, Areedj I (African Journal of Infectious Diseases (AJID), 2013)
Carbapenemases are being increasingly reported in Enterobacteriaceae including Klebsiella pneumoniae. Infection with carbapenemase-producing organisms has caused considerable increases in morbidity and mortality with limited therapeutic options. Issues related to difficulties associated with pathogen identification and infection control have been identified as major obstacles to the control of these multi-drug resistant organisms. Identification of this enzyme in organisms not previously found to harbor them has added to the already existing challenge in the control of this growing problem. The case of a 60 year-old Saudi lady with diabetes, hypertension, pituitary adenoma, hypothyroidism, and obstructive sleep apnea who was admitted in the ICU following a cardiac arrest is hereby presented. During the course of her treatment she acquired various infections that led to her exposure to antimicrobials from almost all classes at various times; including bacteremia due to a pan-drug resistant Klebsiella pneumoniae and multi-drug resistant Acinetobacter baumannii. She was successfully treated using a combination of colistin and amikacin. This case highlights the resurgence of colistin in clinical practice and also calls for the need to expand our antibiogram to include antibiotics not conventionally reported, especially in areas where drug resistance is a growing problem. Improving susceptibility detection methods for Klebsiella pneumoniae and hand hygiene could prove effective in reducing nosocomial infections. Involvement of clinical pharmacists in antimicrobial stewardship could reduce the development of antimicrobial drug resistance. Key words: bacteremia, carbapenemases, pan-drug resistance, Klebsiella pneumoniae, colistin.